The Role of Ku70 as a Cytosolic DNA Sensor in Innate Immunity and Beyond - Sui, Hongyan; Hao, Ming; Chang, Weizhong; Imamichi, Tomozumi (Frontiers in Cellular and Infection Microbiology, 2021)
Human Ku70 is a well-known endogenous nuclear protein involved in the non-homologous end joining pathway to repair double-stranded breaks in DNA. However, Ku70 has been studied in multiple contexts and grown into a multifunctional protein. In addition to the extensive functional study of Ku70 in DNA repair process, many studies have emphasized the role of Ku70 in various other cellular processes, including apoptosis, aging, and HIV replication. In this review, we focus on discussing the role of Ku70 in inducing interferons and proinflammatory cytokines as a cytosolic DNA sensor. We explored the unique structure of Ku70 binding with DNA; illustrated, with evidence, how Ku70, as a nuclear protein, responds to extracellular DNA stimulation; and summarized the mechanisms of the Ku70-involved innate immune response pathway. Finally, we discussed several new strategies to modulate Ku70-mediated innate immune response and highlighted some potential physiological insights based on the role of Ku70 in innate immunity.